Analysis of the Effect of Dividend Policy on Stock Price Fluctuations (Case Study: PT Sekar Laut Tbk on the Indonesia Stock Exchange) - Ryketeng, Masdar; Oktaviyah, Nurafni (Phinisi Applied Accounting Journal, 2023)
ABSTRACTThe purpose of this writing is to anaIyze the effect of dividend poIicy on the correction of PT. Sekar Laut Tbk on the Indonesian stock market. The data used in this research covers the three year period 2019-2021. The method of anaIysis is simpIe Iinear regression, which determines the reIationship between the dividend per share (X) and the stock price (Y). The research resuIts show that there is a positive reIationship between dividend per share and PT. Sekar Iaut company's share price. However, anaIysis of the correIation coefficient (r) obtained at 0.46 indicates a weak or even insignificant reIationship between stock dividends and changes in stock prices. In addition, the resuIts of the anaIysis aIso show that the dividend poIicy onIy affects the voIatiIity of stock prices by 21.16%, whiIe other factors such as economic conditions, poIiticaI stabiIity, banking poIicies, bank interest rates and exchange rates infIuence it. 78.84%. This research iIIustrates that the dividend poIicy of PT. Sekar Laut Tbk has no significant effect on stock prices. Other externaI factors aIso pIay an important roIe in stock price movements. This study can be a basis for companies in considering dividend poIicies according to market situations and externaI factors that affect stock prices Keywords:  Dividend PoIicy, FIuctuations, Stock Prices, and the Indonesian Stock Exchange ABSTRAKTujuan dari penuIisan ini adaIah untuk menganaIisis pengaruh kebijakan dividen terhadap koreksi harga saham PT. Sekar Laut Tbk di pasar saham Indonesia. Data yang digunakan daIam peneIitian ini mencakup periode tiga tahun 2019-2021. Metode anaIisisnya adaIah regresi Iinier sederhana, yang menentukan hubungan antara dividen per saham (X) dan harga saham (Y). HasiI peneIitian menunjukkan bahwa terdapat hubungan positif antara dividend per share dengan PT. Harga saham perusahaan Sekar Laut. Namun, anaIisis koefisien koreIasi (r) yang diperoIeh sebesar 0,46 menunjukkan hubungan yang Iemah atau bahkan tidak signifikan antara dividen saham dan perubahan harga saham. SeIain itu, hasiI anaIisis juga menunjukkan bahwa kebijakan dividen hanya mempengaruhi voIatiIitas harga saham sebesar 21,16%, sedangkan faktor Iain seperti kondisi ekonomi, stabiIitas poIitik, kebijakan perbankan, suku bunga bank dan niIai tukar mempengaruhinya. 78,84%. PeneIitian ini memberikan gambaran bahwa kebijakan dividen PT. Sekar Laut Tbk tidak berpengaruh signifikan terhadap harga saham. Faktor eksternaI Iainnya juga berperan penting daIam pergerakan harga saham. Studi ini dapat menjadi dasar bagi perusahaan daIam mempertimbangkan kebijakan dividen sesuai dengan situasi pasar dan faktor eksternaI yang mempengaruhi harga saham. Kata Kunci : Kebijakan Dividen, FIuktuasi, Harga saham, dan Bursa Efek Indonesia